0
$\begingroup$

I use $v=y^{\prime}$ and get a first order non-linear ODE, then how to solve $(y^{\prime})^2=\frac{2}{3}y^3-2y^2+\frac{4}{3}$?

$\endgroup$
  • 1
    $\begingroup$ Something is wrong here. The condition $y'=0$ means that the function is constant, and makes everything trivial. Also if $y'=0$, then how can $y'(x_0)$ be $2$? $\endgroup$ – A. Pongrácz Aug 8 '18 at 9:32
1
$\begingroup$

$(y^{\prime})^2=\frac{2}{3}y^3-2y^2+\frac{4}{3}$ is false.

The correct way is with $\frac{dy}{dx}=v(y)$ and $\frac{d^2y}{dx^2}=\frac{dv}{dy}\frac{dy}{dx}=v\frac{dv}{dy}=v\,v'$ $$vv'=y^2-y$$ $$v^2=\int(2y^2-2y)dy$$ $$(y')^2=\frac23 y^3-y^2+c$$

OR EQUIVALENTLY : $$y''=y^2-y$$ $$2y''y'=2y^2y'-2yy'$$ $$(y')^2=\frac23 y^3-y^2+c$$

Condition :

$y'(x_0)=2$ and $y(x_0)=1$ implies $2^2=\frac23-1+c$ hence $c=\frac{13}{3}$ $$y'=\sqrt{\frac23 y^3-y^2+\frac{13}{3}}$$ $$\int\frac{dy}{\sqrt{\frac23 y^3-y^2+\frac{13}{3}}}=x+C$$ $C$ has to be determined according to the condition $y(x_0)=1$. $$\int_1^y\frac{d\theta}{\sqrt{\frac23 \theta^3-\theta^2+\frac{13}{3}}}=x-x_0$$

This is an elliptic integral. One cannot go further with elementary functions.

If it is an academic exercise supposing a solution with elementary functions one can suspect that there is a mistake in the wording of the problem.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.